Pengaruh Struktur Modal, Ukuran Perusahaan, Book Tax Differences dan Investment Opportunity Set Terhadap Kualitas Laba - Pretty Prycellia Herlambang; Muhammad Abdul Aris (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Earnings quality is an important measure in accounting and finance because it reflects the integrity of the company’s financial reports. This research aims to determine the influence of capital structure, company size, book tax differences and investment opportunity set on earnings quality in manufacturing companies listed on IDX in 2021-2023. The sampling method used in this research was a purposive sampling method and 123 data were obtained as the final sample. The data analysis technique is multiple linear regression analysis with SPSS version 25. The results of the research show that the variables company size and book tax differences have a significant effect on earnings quality. Meanwhile, capital structure and investment opportunity set do not have a significant on earnings quality.